Uma nova estratégia de controle baseado em modelo de perdas para melhoria de eficiência energética em motores de indução - Pelegrin, Jessé de (2013)
This paper develops a new method of controlling the drive energy efficiency of induction motors . This technique uses a model of losses and a control structure based on minimum energy consumption . At first , studies with the main drivers of energy efficiency in the last decade are presented . Then the electrical and mechanical models of three-phase induction motor are presented , from the classic model , with the reference axis qd0 . The controller used is an indirect field-oriented control (IFOC), composed of an outer control loop speed and flow , and an inner current control loop , showing a good performance of torque and speed. Because it is a IFOC controller, where the engine parameters are critical to obtain good results , the testing of induction motor is carried out and presented . Knowing the main sources of losses of the engine, the controller of energy efficiency can be drawn . The loss model based (LMC) controller is described , as well as the controller recursive search (SC), both widely used in the literature . The LMC proposed is implemented through optimum standard curves of flow based on power absorbed. Depending on the load on the motor shaft , a new standard curve is used . The proposed controller called efficiency ( MBC - Model Based Control ) uses the LMC method with a IFOC controller , this is simulated via textit software emph Matlab and verified experimentally through a platform drive designed and assembled , as the project described . The controller proposed efficiency is compared with the drive and the constant flow controller SC to different profiles of the axle. For all cases, the proposed controller showed the best performance of the machine.